Carbon dioxide emission, institutional quality, and economic growth: empirical evidence from Malaysia / Lin-Sea Lau, Chee-Keong Choong and Yoke-Kee Eng - Lin Sea, Lau; Chee-Keong, Choong; Yoke-Kee, Eng (Faculty of Administrative Science and Policy Studies, 2012)
In view of Malaysia’s status as a fast-growing economy with accelerating carbon dioxide emissions, a better understanding of the relationship between economic growth and pollution is vital to the policy makers. This paper, therefore, attempts to investigate the existence of long run relationship among carbon dioxide emission, institutional quality, exports, and economic growth and further examines the causal relationship among these variables in Malaysia for the period 1984-2008. For the purpose of this study, both autoregressive distributed lag (ARDL) bound testing approach and Granger causality tests are employed. From the bounds test, it is found that a long run relationship does exist among the variables, even using different conditioning information sets. A positive and significant interaction term between carbon dioxide emission and institutional quality indicator (i.e. law and order) implies that good institutional quality is important in controlling carbon dioxide emission in the process of economic development. The results for Granger causality tests further confirm the importance of institutional frameworks in reducing carbon dioxide emissions since institutional quality is found not only affects economic growth directly, but also indirectly via carbon dioxide emissions. This indicates that sound institutional frameworks are essential for Malaysia to achieve high economic growth without sacrificing its environment.